Determinants of leisure-time physical activity: Evidence from Malaysia - Cheah, Yong Kang; Tan, Andrew K. G. (World Scientific Publishing Co., 2014)
This paper examines how socio-demographic and health-lifestyle factors determine participation and duration of leisure-time physical activity in Malaysia.Based on the Malaysia Non-Communicable Disease Surveillance-1 data, Heckman's sample selection model is employed to estimate the probability to participate and duration on physical activity.Results indicate that gender, age, years of education and family illness history are significant in explaining participation probability in leisure-time physical activity.Gender, income level, smoking-status and years of education are significant in explaining the weekly duration conditional on participation, whereas smoking-status and years of education are significant in determining the unconditional level of leisure-time physical activity.